Penalaran Matematis Mahasiswa Calon Guru SD dalam Menyelesaikan Soal Problem Solving - Anton Budi Jatmiko; Erry Hidayanto; Abdur Rahman As’ari (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This paper examines the mathematical reasoning ability of prospective educator understudies in taking care of issues as problem solving. This paper aims to analyze how far the mathematical reasoning abilities of elementary school teacher candidates in solving problem solving problems. This study uses a qualitative approach with descriptive research. The results of this study indicate that the responses of prospective elementary school teacher students in solving problem solving problems are different at each level. The response can reflect the students' mathematical reasoning ability in solving problem.Abstrak: Makalah ini menganalisis kemampuan penalaran mahasiswa calon guru sekolah dasar dalam menangani soal pemecahan masalah. Tulisan ini bermaksud mengkaji seberapa jauh kemampuan penalaran matematis calon guru SD dalam mengerjakan soal pemecahan masalah. Ulasan ini menggunakan metodologi kualitatif dengan penelitian deskriptif. Efek samping dari tinjauan ini menunjukkan bahwa reaksi mahasiswa calon guru sekolah dasar dalam menangani masalah berbeda di setiap tingkat. Respon tersebut dapat mencerminkan kemampuan penalaran mahasiswa dalam mengatasi masalah.